A modified free chimeric osteocutaneous fibular flap design for head and neck reconstruction: Experience on a series of 10 cases. Issue 6 (29th July 2013) - Roan, Tyng‐Luen; Chen, Chien‐Chang; Yu, Yen‐Chen; Hsieh, Jung‐Hsien; Horng, Shyue‐Yih; Tai, Hao‐Chih; Cheng, Nai‐Chen; Chien, Hsiung‐Fei; Tang, Yueh‐Bih
<x xml:space="preserve">Abstract</x> Background We have previously described a modified chimeric fibular osteocutaneous flap design based on a combination of a traditional fibular flap and a peroneal artery perforator fasciocutaneous flap for mandible and adjacent soft tissue reconstruction. The purpose of this article is to share our experience with a larger case series utilizing this new technique for mandible and adjacent soft tissue reconstruction after cancer wide excision surgery and a more detailed description on these flaps harvesting procedures. Patients and methods Ten patients (age range from 32 to 63 years), who had segmental defect of mandible and adjacent soft tissue defect after cancer wide excision surgery, received mandible and adjacent soft tissue reconstruction based on the modified chimeric fibular flap design. Results The skin paddle based on peroneal perforators ranged from 9 cm × 3.5 cm to 10 cm × 10 cm and the mean pedicle length was 8.9 cm. Four patients underwent primary closure of the donor site. Three flap salvage procedures were performed due to vascular thrombosis and all flaps survived well. Nine patients had acceptable outer appearance, and one patient complained of cheek sunken. All patients had at least 3‐cm interincisor distance during a mean of 12‐month follow‐up period. Conclusion The modified chimeric osteocutaneous fibula flaps were feasible design with few intermuscular septum problems during bone fixation. Furthermore, it provided larger skin paddles with few restrictions to reconstruct the cheek skin defect. © 2013 Wiley Periodicals, Inc. Microsurgery 33:439–446, 2013.